2021
DOI: 10.3389/fendo.2021.702482
|View full text |Cite
|
Sign up to set email alerts
|

Graves’ Disease and Rheumatoid Arthritis: A Bidirectional Mendelian Randomization Study

Abstract: BackgroundThe frequent coexistence of Graves’ disease (GD) and rheumatoid arthritis (RA) has been cited and discussed in observational studies, but it remains a question as to whether there is a causal effect between the two diseases.MethodsWe retrieved genome-wide association study (GWAS) summary data of GD and RA from BioBank Japan (BBJ). Single nucleotide polymorphisms (SNPs) associated with diseases of interest were selected as instrumental variables (IVs) at a genome-wide significance level (P < 5.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 37 publications
(59 reference statements)
1
19
0
Order By: Relevance
“…It is reasonable to speculate that thyroid dysfunction shares a common pathogenesis with RA (59). Exploring the co-pathogenesis pathway of these two diseases and appropriate application of drugs that can act on the co-pathogenesis targets may be an ideal way to prevent and treat co-diseases in the future (58,60). In addition, a study by Raterman et al also emphasized the need for careful drug selection in patients with RA complicated by autoimmune thyroiditis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reasonable to speculate that thyroid dysfunction shares a common pathogenesis with RA (59). Exploring the co-pathogenesis pathway of these two diseases and appropriate application of drugs that can act on the co-pathogenesis targets may be an ideal way to prevent and treat co-diseases in the future (58,60). In addition, a study by Raterman et al also emphasized the need for careful drug selection in patients with RA complicated by autoimmune thyroiditis.…”
Section: Discussionmentioning
confidence: 99%
“…The vast majority of hypothyroidism is caused by autoimmune diseases, such as Hashimoto’s thyroiditis, whereas autoimmune diseases lead to hyperthyroidism in relatively few cases and are influenced by age and environmental factors ( 57 ). A study using Mendelian randomization found a bidirectional causal relationship between RA and Graves’ disease, and good treatment and management of one may benefit the other ( 58 ). It is reasonable to speculate that thyroid dysfunction shares a common pathogenesis with RA ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…To date, no studies, to our knowledge, have been conducted to investigate the role of TL in Graves’ disease. A recent study showed that the relationship between Graves’ disease and rheumatoid arthritis, implying that these two autoimmune diseases were likely to share similar underlying mechanisms ( 42 ). Inflammation and oxidative stress are recognized as parts of the process for most of these diseases, but their molecular mechanisms have not fully been understood.…”
Section: Discussionmentioning
confidence: 99%
“…MR–Egger has low statistical power, so the focus is more on direction and effect ( Luo et al, 2020 ; Cai et al, 2021 ). The weighted median provided a reliable Mendelian evaluation when 50% of the instrumental variables (instrument variables) were not valid ( Wu et al, 2021 ). The odds ratio (OR) and 95% confidence interval (CI) were used to assess the relative risk due to the presence of the disease of interest.…”
Section: Methodsmentioning
confidence: 99%